ROCKA(GOOD)BYE HAMLET: A DISCUSSION OF THE FLOP ROCK MUSICAL ROCKABYE HAMLET (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2022)
This paper focuses on Rockabye Hamlet, a 70s rock-musical adaptation of Shakespeare's Hamlet.This piece discusses the musical's shortcomings and the political pitfalls of the theatre industry itself, which aided in the musical's demise and rather short life-span. The essay analyzes what the creative team could have done better to allow the show to thrive in an environment where it was simultaneously set up to fail.For additional context, listen to the author's reflection on the piece below.